2019
DOI: 10.17241/smr.2019.00339
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Psychological Distress between Patients with Periodic Limb Movement Disorder and Restless Legs Syndrome

Abstract: Background and ObjectiveaaWe used the Symptom Checklist 90-Revised (SCL-90-R) to compare the psychosomatic symptom profiles between periodic limb movement disorder (PLMD) and restless legs syndrome (RLS) patients. MethodsaaTwenty consecutive drug-naïve RLS patients, 20 age-and sex-matched patients with PLMD and healthy controls were enrolled. Questionnaires evaluating sleep (Pittsburgh Sleep Quality Index, and Insomnia Severity Index), depression (Beck Depression Inventory II), and psychosomatic symptoms (SCL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Interestingly, another Korean study reported significantly more severe anxiety and depressive symptoms in RLS patients with lower PLMI (129). In keeping, another study that compared neuropsychiatric symptoms in patients with PLMD to those with RLS highlighted a higher psychosomatic burden in the RLS patients (130). In this study, RLS patients also showed a higher somatization burden (130).…”
Section: Associated Psychiatric and Neurologic Disorderssupporting
confidence: 62%
See 1 more Smart Citation
“…Interestingly, another Korean study reported significantly more severe anxiety and depressive symptoms in RLS patients with lower PLMI (129). In keeping, another study that compared neuropsychiatric symptoms in patients with PLMD to those with RLS highlighted a higher psychosomatic burden in the RLS patients (130). In this study, RLS patients also showed a higher somatization burden (130).…”
Section: Associated Psychiatric and Neurologic Disorderssupporting
confidence: 62%
“…In keeping, another study that compared neuropsychiatric symptoms in patients with PLMD to those with RLS highlighted a higher psychosomatic burden in the RLS patients (130). In this study, RLS patients also showed a higher somatization burden (130). Future prospective studies should closely examine whether PLMS status has any bearing on the paindepression-anxiety relationship in RLS, and whether it independently predisposes for any distinct neurologic or psychiatric phenotype.…”
Section: Associated Psychiatric and Neurologic Disordersmentioning
confidence: 51%
“…Of the included studies, eight were conducted in Turkey ( 22–24 , 26 , 28 , 29 , 31 , 40 ), three in Korea ( 30 , 35 , 38 ), two in Spain ( 25 , 32 ), two in Germany ( 27 , 36 ), two in China ( 9 , 34 ), one in Austria ( 33 ), one in France ( 37 ), one in Italy ( 39 ), and one in America ( 41 ).…”
Section: Resultsmentioning
confidence: 99%